1999
DOI: 10.1063/1.478449
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular dynamics diffusion theory approach to complex unimolecular reactions

Abstract: A theory for nonisothermal unimolecular reaction rates We consider the relation between observed pump-probe signals in the femtosecond regime and the kinetics of unimolecular reactions, that is, the exponential decay of reactants and the exponential rise of the product population, respectively. It is shown that the signals cannot be fully accounted for within standard approaches of unimolecular decay, conventionally used in the past, since interference effects between the quasi-bound vibrational states within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…For us, BXD has its origin in the intramolecular dynamics diffusion theory (IDDT) [ 4 8 ], which has demonstrated that long-time reaction rates can be recovered from a set of short-time MD simulations [ 8 ]. Longer time-scale dynamics may be calculated from the set of rate constants obtained from short-time simulations within each box.…”
Section: Introductionmentioning
confidence: 99%
“…For us, BXD has its origin in the intramolecular dynamics diffusion theory (IDDT) [ 4 8 ], which has demonstrated that long-time reaction rates can be recovered from a set of short-time MD simulations [ 8 ]. Longer time-scale dynamics may be calculated from the set of rate constants obtained from short-time simulations within each box.…”
Section: Introductionmentioning
confidence: 99%
“…The present approach enables us to extend our previous studies [10][11][12][13][14] of IVR-controlled reactions to the more general case whether the rate of IVR is faster or slower than the rate of reaction. Assuming constant friction, the method predicts the rate constants for a wide range of energies by requiring only one rate from a trajectory calculation at a single energy to determine the friction coefficient.…”
Section: Discussionmentioning
confidence: 97%
“…16 We have applied the energy diffusion theory to compute the microcanonical rates for large molecules in the high-energy (diffusion) regime by assuming that the IVR rate is much slower and thus determines the dynamic rate. [11][12][13][14] The present approach enables us to obtain the reaction rates more generally for the entire range of energies from the statistical to the diffusion limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the idea of intrinsic reaction coordinate, We have applied it to the case of ring fission in RDX ͑hexahydro-1,3,5-trinitro-1,3,5-triazine͒ molecule where the reaction coordinate is a combination of several modes, and have obtained good agreement with trajectory simulations. 18 This suggests that the method may be generally applicable to a wide range of problems.…”
Section: Concluding Remarkmentioning
confidence: 99%